1994
DOI: 10.1021/bi00189a008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the ATPase Activity of Purified Chinese Hamster P-glycoprotein

Abstract: A simple and rapid procedure is described for purification of P-glycoprotein (Pgp) from a multidrug-resistant Chinese hamster ovary cell line (CR1R12) in which the plasma membranes are highly enriched in Pgp (Al-Shawi, M.K., Senior A.E. (1993) J. Biol. Chem, 268, 4197-4206). The procedure consisted of octylglucoside solubilization of Pgp from plasma membranes and chromatography on Reactive Red 120 agarose. The purified Pgp displayed substantial verapamil-stimulated MgATPase activity (kcat = 9.2 s-1, KM(MgATP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

38
191
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(229 citation statements)
references
References 37 publications
38
191
0
Order By: Relevance
“…4), PgP had been purified using conditions optimized for its own recovery, and the preparation showed a basal ATPase activity and response to substrate consistent with what one expects for the fully functioning molecule (Table I). As a consequence, we conclude that nucleotide binding by CFTR is comparable to that shown by Pgp [36,38]. We also note that CFTR catalyzes a net hydrolysis of ATP (Fig.…”
Section: Purification Of Functional Cftrsupporting
confidence: 64%
See 3 more Smart Citations
“…4), PgP had been purified using conditions optimized for its own recovery, and the preparation showed a basal ATPase activity and response to substrate consistent with what one expects for the fully functioning molecule (Table I). As a consequence, we conclude that nucleotide binding by CFTR is comparable to that shown by Pgp [36,38]. We also note that CFTR catalyzes a net hydrolysis of ATP (Fig.…”
Section: Purification Of Functional Cftrsupporting
confidence: 64%
“…Indeed, when the data were expressed on a molar basis (with correction for protein content and molecular weight), we concluded that CFTR and Pgp bind nucleotide (Az-ATP) with approximately equal efficiency (109% vs. 100%, respectively). Since the biochemical characteristics of Pgp purified from Sf9 cells (e.g., V max , K M , and substrate stimulation) match values cited in the literature for the fully functioning molecule [33,[35][36][37][38] (Table I), we conclude that nucleotide processing by purified CFTR exhibits characteristics similar to that of Pgp.In mammalian systems, R domain phosphorylation must occur before CFTR chloride channel function is observed. However, in Sf9 cells, the CFTR-mediated anion conductance appears without addition of exogenous stimuli that might activate intracellular protein kinases and promote R domain phosphorylation [13].…”
supporting
confidence: 71%
See 2 more Smart Citations
“…Both halves of P-gp can hydrolyze ATP (14,15), but drug-stimulated ATPase activity (14) and conferring of drug resistance (16) requires interaction between the two halves of P-gp. Both halves of P-gp are required for activity because drug binding requires interaction between the NH 2 and COOHterminal TM domains (16) whereas both ATP binding sites are needed for ATPase activity (17)(18)(19)(20)(21) and the nucleotide-binding sites appear to function in an alternating mechanism (22).…”
mentioning
confidence: 99%